Association between vaccination with the BNT162b2 mRNA COVID-19 vaccine and Bell's palsy: a population-based study - Rana Shibli; Ofra Barnett; Zomoroda Abu-Full; Naomi Gronich; Ronza Najjar-Debbiny; Ilana Doweck; Gad Rennert; Walid Saliba (Elsevier, 2021)
ABSTRACT: Background: An excess risk of Bell's palsy has been suggested after mRNA vaccines. We examined the association between the BNT162b2 mRNA COVID-19 vaccine and Bell's palsy. Methods: Using the database of the largest healthcare provider in Israel, we retrieved data from different periods in 2018-2021. Observed cases of Bell's palsy occurring within 21-days after the first vaccine dose and within 30-days after the second vaccine dose were compared to the expected cases, based on the experience of the population in 2019. Standardized incidence ratios (SIRs) and attributable risks (ARs) were computed. Findings: Overall, 132 cases of Bell's palsy were reported in 2,594,990 vaccinees with the first dose, and 152 cases in 2,434,674 vaccinees after the second dose. The age and sex weighted SIRs were 1.36(95% CI, 1.14-1.61) and 1.16(0.99-1.36) after the first and second vaccine dose, respectively. SIRs tended to be higher in older age groups after the first and second vaccine doses. The estimates were more pronounced in older females after the first vaccine dose; SIR=1.71(1.10-2.54) at age 45-64, and 2.51(1.65-3.68) at age ≥65 years. The highest AR was 4.46 per 100,000 vaccinees detected in females aged ≥65 years. In patients with previous history of Bell's palsy, only 4 cases of Bell's palsy were reported in 7,567 vaccinees and 10 cases in 7,045 vaccinees after the first and the second dose, respectively. The age and sex weighted SIRs were 1.15(0.36-2.76) and 2.15(1.09-3.83) after the first and second vaccine dose, respectively. Interpretation: This study suggests that the BNT162b2 mRNA COVID-19 vaccine might be associated with increased risk of Bell's palsy. The small estimated attributable risks suggest that the impact on public health is relatively minor. The benefits of vaccinations explicitly outweigh the possible link to Bell's palsy that has high recovery rate if timely treated with corticosteroids. Funding: No external funding was available for this study.